IoT Berbasis NodeMCU ESP8266 Sebagai Decision Support System Pengelolaan Energi Gedung Telkomsel Renon - Hardiansyah, Amien Harist; Kumara, I Nyoman Satya; Hartati, Rukmi Sari (Majalah Ilmiah Teknologi Elektro, 2024)
The Telkomsel Renon Building serves as the regional telecommunications service office for the Bali and Nusa Tenggara area, covering an area of 5072 m2 with a PLN power capacity of 555 kVA. PT Telkom is committed to reducing energy consumption by implementing ISO 50001 energy management. Despite this, the use of 14 smart meters is still manually conducted, leading to a lack of real-time energy usage information. PLN data indicates an average energy consumption from 2017 to 2023 of 628.271 kWh, with an average annual cost of Rp. 696.915.017. Factors such as electrical equipment, room size, activities within, and building insulation affect the building's energy consumption. Inappropriate activities relative to room capacity can lead to energy wastage. One solution proposed for accurately monitoring energy usage in real-time involves the development of an Internet of Things (IoT) based application using Blynk. IoT is implemented in large meeting rooms with Central Split Duct AC and small meeting rooms with Split Wall AC. Measurement results indicate significantly higher energy consumption in large meeting rooms, reaching 4207.83 kWh, compared to only 467.06 kWh in small meeting rooms for similar activities. Discussions with users of small meeting rooms revealed their comfort and successful achievement of meeting objectives. By utilizing small meeting rooms, energy consumption can be reduced by up to 88.9%. Based on these findings, recommendations for room usage SOPs have been formulated for the Telkomsel Renon Building to realize energy-efficient practices towards green building standards. Keywords: Energy Management; Green Building; Internet of Things; Smart Meter.